Production And Characterization Of Amylase Enzyme Isolated From Aspergillus Niger Mtcc-104 Employing Solid State Fermentation - A. KUMAR; J.S. DUHAN (International Journal of Pharma and Bio Sciences, 2011)
Aspergillus strains obtained from IMTECH Chandigarh and from Department of Biotechnology, CDLU, Sirsa were screened for their ability to produce amylase by starch agar plate method. Among the five strains, A. niger MTCC-104 showed highest clearing zone on starch agar plates as well as amylase activity in solid state fermentation. Different substrates like wheat bran, rice bran, soybean meal and black gram bran were screened for enzyme production. Rice bran was found to be the best substrate for the enzyme production. This rice bran supplemented with aqueous salt solution was used for further studies of amylase production and characterization. The enzyme amylase was found to be thermo-stable and active at wide range of pH. Enzyme showed maximum activity at 700C.